StudentsÔÇÖ Competency as Candidates of Guidance and Counseling Counselors in the Implementation of Group Guidance Services - Rahmawati, Suci; Dasril, Dasril; Irman, Irman; Yulitri, Rina (Universitas Islam negeri Mahmud Yunus Batusangkar, 2021)
This study aims to determine the competence of BK (Guidance and Counseling) students as prospective counselors in implementing group guidance services (BKp). This study used a descriptive quantitative method. The sample was determined by using a purposive sampling technique. Likert scale model was chosen as the instrument of this research. The research subjects were BK students of IAIN Batusangkar in the 2019/2020 academic year. The results revealed that the studentsÔÇÖ competency in implementing group guidance services are divided into four categories, they are the competence at transitional stage which is the lowest (63%), competence at activity stage which is in high category (83%), competence at conclusion is categorized low (73%), and last competence at the final stage which is moderate (77%). The research findings have an impact on producing reliable prospective counselors in the future by having the competence to provide group guidance services.